Two new species of Scytinostroma (Russulales, Basidiomycota) in Southwest China - Zhang, Qiu-Yue; Liu, Hong-Gao; Bian, Lu-Sen; Chen, Qian (Frontiers in Cellular and Infection Microbiology, 2023)
Two new species of Scytinostroma viz. S. acystidiatum and S. macrospermum, are described from southwest China. Phylogeny based on ITS + nLSU dataset demonstrates that samples of the two species form two independent lineages and are different in morphology from the existing species of Scytinostroma. Scytinostroma acystidiatum is characterized by resupinate, coriaceous basidiomata with cream to pale yellow hymenophore, a dimitic hyphal structure with generative hyphae bearing simple septa, the absence of cystidia, and amyloid, broadly ellipsoid basidiospores measuring 4.7–7 × 3.5–4.7 μm. Scytinostroma macrospermum is characterized by resupinate, coriaceous basidiomata with cream to straw yellow hymenophore, a dimitic hyphal structure with generative hyphae bearing simple septa, numerous cystidia embedded or projecting from hymenium, and inamyloid, ellipsoid basidiospores measuring 9–11 × 4.5–5.5 μm. The differences between the new species and morphologically similar and phylogenetically related species are discussed.